Association between copper exposure and renal fibrosis in patients with chronic kidney disease: evidence from Mendelian randomization and a retrospective study - Kaixiang Liu; Min Yu; Yangyang He; Ting Wang; Honghua Hu; Zhengwei Wan; Ping Shuai; Shasha Chen; Guisen Li; Li Wang; Xiang Zhong (Frontiers in Public Health)
BackgroundChronic kidney disease (CKD), a global health challenge, is closely linked to renal fibrosis progression. Copper, an essential trace element, influences cellular functions, yet its role in CKD-related fibrosis remains unclear. This study explores the causal relationship between serum copper levels and renal fibrosis in CKD.MethodsA two-sample Mendelian Randomization (MR) analysis integrated GWAS and FinnGen data. Serum copper and other metals were quantified via ICP-MS in 505 CKD patients and 50 controls. Renal fibrosis was histologically assessed in 168 biopsy-confirmed cases. Multivariable logistic regression and restricted cubic splines (RCS) evaluated associations between copper levels, renal function, and fibrosis severity, adjusting for demographics and biochemical parameters.ResultsMR confirmed causality between elevated copper and CKD risk. CKD patients had higher serum copper than controls (957.10 ± 273.82 vs. 795.50 ± 143.85 ng/ml, p < 0.001), with progressive increases from stage 1 to 5 (p < 0.001). In biopsy-proven cases, severe fibrosis (>5%) correlated with higher copper levels and lower eGFR versus mild fibrosis (≤5%). Adjusted analysis identified quartile 4 copper levels (>961.64 ng/ml) as an independent predictor of severe fibrosis (OR = 2.75, 95% CI: 1.06–7.16, p < 0.001). RCS revealed non-linear relationships between copper, fibrosis (P for non-linear = 0.038), and eGFR (P for non-linear = 0.005).ConclusionElevated serum copper is independently associated with renal fibrosis in CKD, suggesting copper dysregulation may contribute to fibrotic pathogenesis. These findings underscore the therapeutic potential of targeting copper metabolism to mitigate CKD progression.